Assessing the value of electric vehicle managed charging: a review of methodologies and results. Issue 2 (7th January 2022) - Anwar, Muhammad Bashar; Muratori, Matteo; Jadun, Paige; Hale, Elaine; Bush, Brian; Denholm, Paul; Ma, Ookie; Podkaminer, Kara
Abstract : Electric vehicle managed charging can benefit all consumers by supporting grid planning, operation, and reliability – especially complementing high-renewable systems. Abstract : Driven by technological progress and growing global attention for sustainability, the adoption of electric vehicles (EVs) is on the rise. Large-scale EV adoption would both disrupt the transportation sector and lead to far-reaching consequences for energy and electricity systems, including new opportunities for significant load growth. Unmanaged EV charging can stress existing grid infrastructure, possibly leading to operational, reliability, and planning challenges both at the bulk and distribution levels. However, effective management of EV charging can resolve these challenges and provide additional value. The demand-side flexibility provided by managed EV charging offers significant potential benefits for the grid over multiple timescales and applications. Managed charging can support power system planning and operations during normal and extreme conditions, benefitting EV owners and other electricity consumers. However, the costs of enabling these services must be weighed against the benefits they provide. We summarize the benefits of managed EV charging, provide an overview of the landscape of existing implementations and costs of managed charging in the United States, critically review the state of the art of methodologies in analysis/modeling studies, and quantify the cost and benefits of managed charging as reported in the reviewed studies. Finally, we distill several key insights outlining the factors affecting the value of managed EV charging and identify critical gaps and remaining challenges to fully realize effective EV-grid integration.